Praktik Arisan Gabah di Kalangan Petani Perspektif Hukum Islam - Rimah; Yayat Hidayat (Al Barakat, 2026)
Rice-Arisan is a community-based rotating savings activity carried out in Bondan Village, Sukagumiwang District, Indramayu Regency. The process of this rice-arisan is conducted twice a year, with contributions paid in the form of rice harvested by the farmers. There is a condition in which the price of rice may fluctuate, while the contribution amount remains unchanged. This study aims to examine how the rice-arisan is practiced in Bondan Village, Sukagumiwang District, Indramayu Regency, and to analyze it from the perspective of Islamic law. The research method used in this study is qualitative research with a field research approach. Data collection techniques employed include interviews and documentation. The results of the study show that: first, in practice, the rice-arisan involves differences in the type and quality of rice, which lead to variations in the sales value. However, there is an agreement among the farmers based on mutual consent at the beginning of the arisan arrangement. Second, from the perspective of Islamic law, the rice-arisan falls under the category of mutual assistance among members and is classified as qardh (loan), as it fulfills the requirement of mutual consent among all participants regarding the contributions. However, it still contains an element of riba (usury), due to the obligation to provide an additional item in the form of cigarettes to the winner, which renders the transaction usurious. In addition, the practice of rice-arisan also contains an element of gharar (uncertainty). Nevertheless, in this context, the gharar is considered minor and does not invalidate the qardh.